The perception of IT organizations towards Software Development Methodology adoption / Fazilahsul Paridalhaisah Mohd Ali - Mohd Ali, Fazilahsul ParidalHaisah (2007)
This study was conducted to investigate the factors that impact the adoption of Software Development Methodology (SDM). This study uses interview and survey instrument to identify the SDM that mostly adopted by IT organizations. The survey focuses on the organizational perspective which is significant to obtain more information in relation to the SDM selection and adoption. Five factors of adoption by Roger's were identified and used to achieve findings in this research. The factors include relative advantage, compatibility, complexity, trialability, and observability. All the relevant data that is valuable to this study will be collected and analyze to reach the possible results. Then, the results will address the methodology used in software development industry, and also the factors that has greater impact to the adoption of that method. The result found that Rapid Application Development (RAD) is the method that mostly adopted by IT organizations. While relative advantage can be the dominant factor that influences the adoption of that method.